How abstraction of a pre-service teacher in constructing relationships among quadrilaterals - Hodiyanto; Budiarto, Mega Teguh; Ekawati, Rooselyna; Susanti, Gemi; Kim, Jeonghyeon; Bonyah, Ebenezer (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Abstraction is essential to learning mathematics because the mathematical concepts obtained through abstraction will be more meaningful than directly receiving these concepts. This study aims to describe the pre-service teachers' abstraction in constructing relationships among quadrilaterals. This research method was explorative qualitative research with a purposive sampling technique. The subject of this research was a pre-service mathematics teacher who had taken a geometry course. The data analysis techniques used in this study were data condensation, data display, drawing and verifying conclusions. The research results showed that the participant used epistemic actions in an abstraction, such as recognising each quadrilateral type, building-with their properties, constructing relationships among them, and consolidating the abstract results made. Thus, the abstraction in constructing relationships among quadrilaterals can be observed from the epistemic actions: recognising, building-with, constructing, and consolidation, known as RBC+C.